Demonstration of an optical phased array using electro-optic polymer phase shifters. (23rd January 2018) - Hirano, Yoshikuni; Motoyama, Yasushi; Tanaka, Katsu; Machida, Kenji; Yamada, Toshiki; Otomo, Akira; Kikuchi, Hiroshi
Abstract: We have been investigating an optical phased array (OPA) using electro-optic (EO) polymers in phase shifters to achieve ultrafast optical beam steering. In this paper, we describe the basic structures of the OPA using EO polymer phase shifters and show the beam steering capability of the OPA. The designed OPA has a multimode interference (MMI) beam splitter and 8-channel polymer waveguides with EO polymer phase shifters. We compare 1 × 8 MMI and cascaded 1 × 2 MMI beam splitters numerically and experimentally, and then obtain uniform intensity outputs from the 1 × 8 beam splitter. We fabricate the EO polymer OPA with a 1 × 8 MMI beam splitter to prevent intensity dispersion due to radiation loss in bending waveguides. We also evaluate the optical beam steering capability of the fabricated OPA and found a 2.7° deflection of far-field patterns when applying a voltage difference of 25 V in adjacent phase shifters.